Investigations on aviadenoviruses isolated from turkey flocks in Germany. Issue 2 (4th March 2017) - Kleine, A.; Hafez, H. M.; Lüschow, D.
ABSTRACT: During routine diagnosis in 2012, 69 samples of diseased turkey breeding and fattening flocks in Germany were examined for infection with aviadenoviruses by virus isolation using primary chicken embryo liver cells. In total, 21 aviadenovirus isolates, identified by a group-specific indirect immunofluorescence test, were obtained from 19 flocks. In almost all cases, molecular typing of these isolates based on partial hexon gene sequences revealed the presence of different types of turkey aviadenoviruses (TAdVs), including species Turkey aviadenovirus B (TAdV-B) with at least two different genotypes, as well as the species Turkey aviadenovirus C (TAdV-C) and Turkey aviadenovirus D (TAdV-D). Further analysis of DNA-dependent DNA polymerase gene sequences confirmed the classification of selected TAdV-C and TAdV-D isolates. Based on the results obtained for both genes, we suggest that TAdV-2, in addition to TAdV-4, belongs to the species TAdV-C. In contrast, amplification of the DNA polymerase gene fragment of nearly all investigated TAdV-B isolates failed due to unknown reasons. The results of sequence and phylogenetic analysis support the previously proposed classification of TAdVs into three different species and demonstrated how widely spread these viruses are in German turkey flocks. Analysis of case histories revealed a wide range of clinical and pathological changes; however an apparent link between types and disease conditions was not identified.